Nonleaching Antibacterial Concept Demonstrated by In Situ Construction of 2D Nanoflakes on Magnesium. Issue 1 (30th September 2019) - Wang, Guomin; Jiang, Wenjuan; Mo, Shi; Xie, Lingxia; Liao, Qing; Hu, Liangsheng; Ruan, Qingdong; Tang, Kaiwei; Mehrjou, Babak; Liu, Mengting; Tong, Liping; Wang, Huaiyu; et al.
Abstract: In bone implants, antibacterial biomaterials with nonleaching surfaces are superior to ones based on abrupt release because systemic side effects arising from the latter can be avoided. In this work, a nonleaching antibacterial concept is demonstrated by fabricating 2D nanoflakes in situ on magnesium (Mg). Different from the conventional antibacterial mechanisms that depend on Mg 2+ release and pH increase, the nanoflakes exert mechanical tension onto the bacteria membranes to destroy microorganisms on contact and produce intracellular stress via physical interactions, which is also revealed by computational simulations. Moreover, the nanoflake layer decelerates the corrosion process resulting in mitigated Mg 2+ release, weaker alkalinity in the vicinity, and less hydrogen evolution, in turn inducing less inflammatory reactions and ensuring the biocompatibility as confirmed by the in vivo study. In this way, bacteria are killed by a mechanical process causing very little side effects. This work provides information and insights pertaining to the design of multifunctional biomaterials. Abstract : Nanoflakes are fabricated that stretch bacteria on contact with assistance of the zigzag structure on the edge. The mechanical stress imposed on bacteria triggers a series of reactions such as membrane rupture and reactive oxygen species burst leading to bacterial death. Biomaterials with the nonleaching antibacterial ability are very promising in implants and cause little side effects and inflammation in vivo.